The application of training monitoring for synchronized swimming - Xu, J.; Zhang, X.; Feng, L.; Lu, Y.; Zhang, L.; Yuan, T.; Wang, N. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
This study is aimed to establish the special sports training monitoring system for synchronized swimming in order to improving the scientific level of its training. The researchs objects are the national synchronized swimming team who are 22.6±2.7 years old. We used the measures of sports physiology, sports biochemistry, sports biomechanics and exercise training to construct this special sports training monitoring system for synchronized swimming. The system is composed of the special sports training load and exercise capacity monitoring systems. The training load monitoring system includes analysis of a set of actions training, training sessions and short or long cyclic training using heart rate, serum creatine kinase levels, body weight and composition, hemoglobin, red blood cell count, white blood cell count, serum testosterone and cortisol levels, the indexes of urine samples and Omega Wave to evaluate the training load intensity and volume. The exercise capacity monitoring system is comprised of basic physical fitness, special sports physical fitness and special sports techniques monitoring systems, to assess the special sports capacity of synchronized swimming athletes via the indexes of exercise training, sports physiology, sports biochemistry and sports biomechanics methods.